Cardiac macrophages in maintaining heart homeostasis and regulating ventricular remodeling of heart diseases - Kang, Mengjie; Jia, Hui; Feng, Mei; Ren, Haolin; Gao, Junjia; Liu, Yueyang; Zhang, Lu; Zhou, Ming-Sheng (Frontiers in Immunology, 2024)
Macrophages are most important immune cell population in the heart. Cardiac macrophages have broad-spectrum and heterogeneity, with two extreme polarization phenotypes: M1 pro-inflammatory macrophages (CCR2 -ly6C hi ) and M2 anti-inflammatory macrophages (CCR2 -ly6C lo ). Cardiac macrophages can reshape their polarization states or phenotypes to adapt to their surrounding microenvironment by altering metabolic reprogramming. The phenotypes and polarization states of cardiac macrophages can be defined by specific signature markers on the cell surface, including tumor necrosis factor α, interleukin (IL)-1β, inducible nitric oxide synthase (iNOS), C-C chemokine receptor type (CCR)2, IL-4 and arginase (Arg)1, among them, CCR2 +/-is one of most important markers which is used to distinguish between resident and non-resident cardiac macrophage as well as macrophage polarization states. Dedicated balance between M1 and M2 cardiac macrophages are crucial for maintaining heart development and cardiac functional and electric homeostasis, and imbalance between macrophage phenotypes may result in heart ventricular remodeling and various heart diseases. The therapy aiming at specific target on macrophage phenotype is a promising strategy for treatment of heart diseases. In this article, we comprehensively review cardiac macrophage phenotype, metabolic reprogramming, and their role in maintaining heart health and mediating ventricular remodeling and potential therapeutic strategy in heart diseases.